2018
DOI: 10.3390/ijms19020493
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Olive Leaf Extract on Acrolein-Exacerbated Myocardial Infarction via an Endoplasmic Reticulum Stress Pathway

Abstract: Many studies reported that air pollution particulate matter (PM) exposure was associated with myocardial infarction (MI). Acrolein representing the unsaturated aldehydes, the main component of PM, derives from the incomplete combustion of wood, plastic, fossil fuels and the main constitute of cigarette smoking. However, the effect of acrolein on MI remains not that clear. In the current study, the effect of acrolein-exacerbated MI was investigated. In vivo, male Sprague–Dawley rats received olive leaf extract … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 55 publications
3
19
0
Order By: Relevance
“…Apoptosis markedly shares in mediation of MI including cleaved caspase‐3, TNFα, and BAX/Bcl‐2 pathway. We found the same in ISO‐ induced MI group, and this is in line with Xu et al , Kumar et al , Jana et al , and Bin‐Jaliah et al .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Apoptosis markedly shares in mediation of MI including cleaved caspase‐3, TNFα, and BAX/Bcl‐2 pathway. We found the same in ISO‐ induced MI group, and this is in line with Xu et al , Kumar et al , Jana et al , and Bin‐Jaliah et al .…”
Section: Discussionsupporting
confidence: 92%
“…This imbalance with the excessive release of reactive oxygen species (ROS) is a major contributing factor in the development of MI. Free radicals attack membrane lipids and mediate a chain of reactions of lipid peroxidation associated with disruption of the structure and permeability of cell membranes .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are studies in the literature proving that olive leaf extract decreases endoplasmic reticulum stress, and thus it may also decrease myocardial infarction [51,52]. A study demonstrated that hydroxytyrosol and oleuropein decreased apoptosis and endoplasmic reticulum stress, induced by acrolein, in cardiomyocyte cells by reducing 78-kDa glucose-regulated protein, the C/EBP homologous protein, and Bax expression levels in rats [52].…”
Section: Lipidemia and Cardiovascular Effectsmentioning
confidence: 99%
“…There are studies in the literature proving that olive leaf extract decreases endoplasmic reticulum stress, and thus it may also decrease myocardial infarction [51,52]. A study demonstrated that hydroxytyrosol and oleuropein decreased apoptosis and endoplasmic reticulum stress, induced by acrolein, in cardiomyocyte cells by reducing 78-kDa glucose-regulated protein, the C/EBP homologous protein, and Bax expression levels in rats [52]. Another study supported the claim that hydroxytyrosol and olive leaf extract reversed the increase in C/EBP homologous protein and 78-kDa glucose-regulated protein expression levels induced by isoproterenol, and it may show cardioprotective effect by means of endoplasmic reticulum stress [51].…”
Section: Lipidemia and Cardiovascular Effectsmentioning
confidence: 99%